BUFFALO REPRODUCTION: PROBLEMS AND CURRENT TECHNOLOGIES - Tappa, Baharuddin (Proceeding Buffalo International Conference, 2013)
The Government of Indonesia has launched to self-sufficient in beef and buffalo meat in Year 2014. However, the reality to day is still importing meat/beef cattle going about 30% of domestic demand. One effort to meet the needs of domestic meat of beef is empowering provision of the needs of beef cattle included buffalo. The domestic water buffalo (Bubalus bubalis) has an important role in the agricultural economy of many developing countries in Asia, including Indonesia providing milk, meat and draught power. The data on the productivity and related aspect of buffalo is relatively scarce even though this livestock has long been raised by farmers over the country. Its population growth rate is not as fast as those of cattle. The lack of buffalo development may be related to many factors and problems ranging from practical husbandry, genetic and environment to the limited attention of the government and animal scientist. Although its reproductive biology is basically similar to that of cattle, there are important differences and unique characteristics that need to be considered in order to apply modern reproductive technologies to improve its productivity. The major reproductive problems affecting buffaloes are mainly as late maturity, long postpartum anoestrous intervals, poor expression of oestrus, poor conception rates (CR) and long calving intervals. Synchronization of time or induction of oestrus can be done using the same regimens as applied in cattle, using various combinations of prostaglandins, progesterone releasing devices, GnRH and eCG, but success rate is poor when treatment is done during the periods of marginal breeding activity or seasonal anoestrus. Embryo technologies such as multiple ovulation embryo transfer, in vitro embryo production, cryopreservation and semen sexing are being intensively studied but have had far lower success rates than in cattle. In line to this facing problem, The Directorate General of Livestock Services, the Department of Agriculture, Republic of Indonesia is now trying to set out some programs that can be optimizing other ruminants such as buffalo to be an alternative livestock for substituting the role of cattle as a main producer of meat. The government of Indonesia was decided regulation of six buffalo cluster according geography and culture.Â This program believes to be benefit for increasing and protecting the buffalo as one of the Indonesia potential genetic diversity (animal germ plasma) from the danger of extinction.